2014
DOI: 10.1080/08959420.2014.854606
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned From a Canadian Province-Wide Age-Friendly Initiative: The Age-Friendly Manitoba Initiative

Abstract: The Age-Friendly Manitoba Initiative was launched in 2008. A formative evaluation we conducted in 2011 with 44 participating rural and urban communities demonstrates considerable progress, with virtually all communities having formed an Age-Friendly Committee and conducting a community assessment to identify priorities for action. The majority of communities implemented one or more age-friendly projects. Major barriers to becoming age-friendly identified by participants included lack of funding; lack of capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 12 publications
2
57
0
Order By: Relevance
“…A consistent finding was the active involvement of older people in their communities as opposed to being passive recipients of services and supports (Keating et al 2013, Menec et al 2014b, Novek & Menec 2014, Walsh et al 2014. However, marginalised older people, who are not active participants in their communities require support and services that are sometimes not available (Keating et al 2013).…”
Section: Collaboration and Partnershipsupporting
confidence: 54%
See 3 more Smart Citations
“…A consistent finding was the active involvement of older people in their communities as opposed to being passive recipients of services and supports (Keating et al 2013, Menec et al 2014b, Novek & Menec 2014, Walsh et al 2014. However, marginalised older people, who are not active participants in their communities require support and services that are sometimes not available (Keating et al 2013).…”
Section: Collaboration and Partnershipsupporting
confidence: 54%
“…For others there was an interdependency between local systems that supported older people (Walsh et al 2014). Additionally, in some small rural communities, there was a perception that people could work together more easily as networks were already in place (Menec et al 2014b). …”
Section: Geographic and Demographic Characteristicsmentioning
confidence: 98%
See 2 more Smart Citations
“…The review identified several narrative accounts of process evaluations of Age-Friendly Initiatives [48][49][50][51]. Despite this finding, there is a gap in knowledge about the holistic impact of Age-Friendly Initiatives on outcomes in the lives of older persons.…”
Section: Age-friendly Citiesmentioning
confidence: 99%